2022
DOI: 10.1001/jamadermatol.2022.0160
|View full text |Cite
|
Sign up to set email alerts
|

Global Burden of Cutaneous Melanoma in 2020 and Projections to 2040

Abstract: ith more than 1.5 million new cases estimated in 2020, skin cancers are the most commonly diagnosed group of cancers worldwide. Malignant melanomas (hereafter melanoma) account for approximately 1 in 5 of these cancers, with approximately 325 000 cases estimated globally in 2020. Historically a rare disease, melanoma incidence rates have been increasing during the last 50 years in fair-skinned populations of European ancestry. 1,2 Much of this increase is likely due to increased exposure of vulnerable populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
343
1
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 556 publications
(358 citation statements)
references
References 64 publications
5
343
1
9
Order By: Relevance
“…Similar to other studies [76], we found that ctDNA detection in blood samples collected in cell stabilising tubes was possible without significant loss of test sensitivity. As these allow a delay in processing of up to 7 days, they can be applied to support ctDNA testing for geographically-remote patients [32], including some Māori [43, 44] and Pacific People [45] who suffer significant cancer outcome inequities in NZ. In addition, ctDNA analysis undertaken in the intervals between surveillance imaging may provide valuable supplementary information to guide clinical care during health service disruptions, such as those introduced during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other studies [76], we found that ctDNA detection in blood samples collected in cell stabilising tubes was possible without significant loss of test sensitivity. As these allow a delay in processing of up to 7 days, they can be applied to support ctDNA testing for geographically-remote patients [32], including some Māori [43, 44] and Pacific People [45] who suffer significant cancer outcome inequities in NZ. In addition, ctDNA analysis undertaken in the intervals between surveillance imaging may provide valuable supplementary information to guide clinical care during health service disruptions, such as those introduced during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand (NZ) where this study is based, people from geographically-remote regions [38] as well as indigenous Māori [39, 40] and Pacific peoples [41], suffer significant inequities in cancer care [42]. In 2020, people in NZ also suffered the highest age-adjusted mortality from metastatic melanoma in the world (5 per 100 000 person-years) [43, 44]. Although the incidence of melanoma in NZ is lower in Māori and Pacific Peoples than in European New Zealanders, Māori and Pacific Peoples on average experience poorer outcomes once diagnosed [45].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Melanoma is uncommon in most African and Asian countries, with most instances having an incidence rate of less than 1 (per 100,000 persons). 9 Although melanoma is more common in white populations, it can occur in other races with low survival rates. 10 In fact, despite recent important advances in prevention, diagnosis and treatment, vast differences in melanoma burden still exist among populations.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma is the cancer of the skin’s pigment cells that caused by abrupt ultraviolet UV radiation from artificial sources or natural sunlight ( 1 , 2 ). The treatment of melanoma is developing rapidly, including complementary disease prevention and detection strategies.…”
Section: Introductionmentioning
confidence: 99%